Students as partners in digital education: Exploring lecture capture in higher education through partnership between students and learning technologists - Luke, Karl; Evans, Geraint (International Journal for Students as Partners, 2021)
This case study reports on two student-staff partnership projects at Cardiff University that explored the student experience of using lecture capture technologies. We describe the background to these projects, how they were designed, and how students and staff worked together to gain insights into the student experience. The case study demonstrates that nuanced understandings regarding the way students use lecture recordings is required and argues that student-staff partnership is an effective way of achieving these understandings. Suggestions are offered regarding how educationists could further harness partnerships to explore the complex interplays between technology and student learning. This reflective account also explores our efforts in achieving meaningful partnership working, the challenges encountered, and highlights the benefits of partnerships between students and professional-services staff, specifically learning technologists.